2010
DOI: 10.1002/pola.23852
|View full text |Cite
|
Sign up to set email alerts
|

Controlled ring‐opening polymerization of lactide by bis‐sulfonamide/amine associations: Cooperative hydrogen‐bonding catalysis

Abstract: The bis‐sulfonamide m‐C6H4(SO2NHPh)2 efficiently promotes the ring‐opening polymerization of lactide when combined with tertiary amines, such as N,N‐dimethylaminopyridine. Polylactides of controlled molecular weights (Mn up to 17,700 g mol−1) and very narrow molecular weight distributions (Mw/Mn < 1.11) are obtained under mild conditions and in a living fashion. The reaction takes place through a bifunctional mechanism involving activation of both the alcohol and the monomer. Modulation of the sulfonamide comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…For the monosulfonamides, it was suggested that low catalyst activity might arise from reduced H-bond donation versus the bis donors. 111 This account is consistent with observations for the mono-, bis-and tris-(thio)urea H-bond donors. 105 Phosphoric and phosphoramidic acids, the weak acidity of which contrasts with strong acids used for electrophilic monomer activated ROP, 13 can act as bifunctional organocatalysts for ROP.…”
Section: Non-(thio)urea Lewis Acid/base Catalysis Sulfonamides Phospsupporting
confidence: 89%
See 1 more Smart Citation
“…For the monosulfonamides, it was suggested that low catalyst activity might arise from reduced H-bond donation versus the bis donors. 111 This account is consistent with observations for the mono-, bis-and tris-(thio)urea H-bond donors. 105 Phosphoric and phosphoramidic acids, the weak acidity of which contrasts with strong acids used for electrophilic monomer activated ROP, 13 can act as bifunctional organocatalysts for ROP.…”
Section: Non-(thio)urea Lewis Acid/base Catalysis Sulfonamides Phospsupporting
confidence: 89%
“…The 18/DMAP cocatalysts produced the most rapid ROP of LA of the HBDs examined, and it was well-controlled. 111 Structurally similar catalysts, 19 and 20, were less active, and no monosulfonamide/base cocatalyzed ROPs of LA have been shown to reach full conversion in 24 h. Neither mononor bis-sulfonamides promoted the ring opening of LA in the absence of an amine cocatalyst. For the monosulfonamides, it was suggested that low catalyst activity might arise from reduced H-bond donation versus the bis donors.…”
Section: Non-(thio)urea Lewis Acid/base Catalysis Sulfonamides Phospmentioning
confidence: 98%
“…5). [18][19][20][21][22] In order to assess the efficiency of these co-catalysts in (Fig. 6) enabled the determination of K app values ( Table 3).…”
Section: Bispidine Synthesis and Lactide Ropmentioning
confidence: 99%
“…For the ROPs of cyclic monomers, such as δ‐valerolactone (δ‐VL), ε‐caprolactone (ε‐CL), LA, and trimethylene carbonate (TMC), the nucleophilic catalysts activated the carbonyl group in the monomers and basic catalysts activated the hydroxyl group in the alcohol initiators and/or polymer chain ends through hydrogen bonding, that is, the chain‐end activation mechanism. In addition, the “bifunctional activation” of a monomer and an initiator was achieved by binary catalyst systems consisting of electrophiles and amines, such as thiourea/amine, sulfonamide/amine, and fluorinated alcohol/amine . In order to achieve the controlled/living ROPs, suitable organocatalysts should be selected according to the type of monomers.…”
Section: Introductionmentioning
confidence: 99%